Acting beyond 2020: better characterization of praziquantel and promising antischistosomal leads. (October 2018) - Panic, Gordana; Keiser, Jennifer
Highlights: Praziquantel safety, efficacy and pharmacokinetics in key demographics are presented. Metabonomic and microbial praziquantel studies inform treatment dynamics. Characteristics of ten promising antischistosomal lead candidates are described. Candidates include the ozonides, old leads and oxamniquine derivatives. Abstract : The commitment to eliminate schistosomiasis as a public health problem has mobilized the expansion of praziquantel treatment to meet the London Declaration targets. New research has thus sought to elucidate praziquantel's safety and efficacy in key demographics such as preschoolers and pregnant women, as well as novel elements of its pharmacokinetics and pharmacodynamics. At the same time, reliance on praziquantel ad infinitum would place schistosomiasis control at risk, should resistance occur. In response, the academic community has been filling the pre-clinical drug discovery pipeline with novel or resurrected drug candidates against schistosomiasis. In this review, we highlight the latest research on praziquantel treatment dynamics, which aims to improve the utility of this important drug. Moreover, we present the most promising preclinical antischistosomal candidates, which should be studied further to achieve the ultimate goal- an alternative antischistosomal drug in the near future.